PECULIARITIES OF THE CONTENT OF PRIMARY SCHOOL TEACHER PROFESSIONAL TRAINING TO WORKING IN MULTILINGUAL ENVIRONMENT IN UKRAINE AND FLANDERS (BELGIUM) - Holovatenko, Tetiana (Educological discourse, 2019)
The article provides a comparative analysis of future primary school teacher training programs to working in a multilingual environment on the example of Artesis Plantijn Hogeschool Antwerpen and Borys Grinchenko Kyiv University. General tendencies in teacher training at the level of content and methodological support are highlighted and systematized. They are the duration of general pedagogical training, competency-based training, interactive learning, individualization of the professional trajectory of the future teacher, interdisciplinary integration at the level of the educational program, the study of foreign languages and teaching methodology. A significant importance before the enrollment to a Hogeschool in Flanders is given to a placement test enabling various types of further individualization of the professional training. In Ukraine individualization is applied after the institutional screening test. As evidenced by a curriculum analysis in both Flanders and Ukraine, study time of general pedagogical subjects is the same. A competency-based approach goes through the entire curriculum up to practical training which occupies a major place in the teacher training process. Teacher training to working in a multilingual environment takes place while learning foreign languages, teaching methodology, and studying socio-cultural modules/subjects. This approach is ensured through interdisciplinary integration within the curriculum. For instance, in Flanders students are offered a multilingual subject program, built as a language maintenance program type A (according to J. Cenoz) in both Dutch and French. In Ukraine students are offered an integrated course of English and teaching methodology. According to the results of our research, multilingual content of teacher training is more developed in Flanders. Therefore, further research of primary school teacher training to working in the multilingual environment in Wallonia and Brussels is needed.